Beberapa Kemungkinan Pengembangan Studi Perbandingan Agama - Noer, Kautsar Azhari (Refleksi: Jurnal Kajian Agama dan Filsafat, 1998)
This text will discuss several possibilities for the development of comparative religion. Comparative religion, as a branch of scientific study of religions, needs attention to ensure that this field can develop well in accordance with innovative academic demands (arising from scientific advancements) and dynamic practical demands (arising from social changes). What possibilities can be pursued to develop comparative religion? These possibilities may include sharing information among scholars, improving the scientific quality of educators, developing and selecting themes, and developing methodologies.